Propagación sexual e injertado de la especie nativa Juglans neotropica Diels en la hacienda “La Florencia” del cantón y provincia de Loja. - Márquez Armijos, Luis Ángel (2024)
J. neotropica Diels is a woody tree that grows between 1 400 and 3 500 m a.s.l. in the countries of Colombia, Ecuador, Peru, Chile, and Argentina. The species is of great cultural importance for its medicinal, textile, food, ornamental, and timber uses, which together with other activities have caused 52% of the natural populations to be overexploited, leading it to be categorized as a threatened species according to the IUCN. For this reason, in search of solutions to mitigate the threats, the present research was carried out in the nursery located in "La Florencia" hacienda in the north of the city of Loja, canton and province of Loja. The objectives were to carry out a comparative analysis of the germination percentage of J. neotropica of two provenances through the application of different pre-germinative treatments, and to determine which provenance of J. neotropica scions used as grafting obtained the highest percentage of budding. For this purpose, fruits and seeds were collected from "Francisco Vivar Castro" Universitario Park (PUFVC) and El Tundo, to which three pre-germinative treatments were applied with boiling water (T1), water and sun (T2) and mechanical (T3) in addition to the control (T0); and the scions were collected from PUFVC and El Zañe. Passing 90 days after sowing the seeds, for PUFVC treatments T2, T3 and T0, and for Tundo T3 and T2 favored germination, unlike T1, with which low germination percentages were obtained, giving an overall average of 47.67 % on river sand, indicating that this is a favorable substrate for this activity. At the end of 60 days after grafting, the PUFVC scions showed a 5.33 % of germination rate, while those of El Zañe showed 0 %, indicating that the diameters of rootstocks and scions should be larger than those used, or that the species is not adapted to this practice.